Fruit frontiers: research on feijoa cultivation in Brazil and Colombia - Moretto, Samira Peruchi; Nodari, Eunice Sueli; Nodari, Rubens Onofre (Diálogos Latinoamericanos, 2022)
In the twentieth century, Latin American countries were persuaded to import projects from the United States that aimed to increase production of basic commodities to supply the international market. As a result, space for agricultural practices of peasants and the cultivation of foodstuffs outside the logic of productivism shrank over time. These alternative practices were maintained in peripheral form, including the production of native fruits, feijoa (Acca sellowiana) among them. Feijoa was chosen due to its unique flavour, aroma and pharmacological and nutritional properties. In this article, we argue that scientific research and small-scale producers, not public policies, were the main drivers of feijoa cultivation in Brazil and Colombia. Scientists supported the increase of production and productivity of a fruit species which remained at the margins of industrial, science-based agriculture. These countries came under heavy international influence to adopt plans intended to modernize their agricultural sector. Despite being on the margins of these development plans and receiving few direct financial subsidies, research on feijoa continued. Today, while Colombia produces monocrops for export, cultivation in Brazil remains incipient and limited to smallholdings.